Introduction to mass communication : media literacy and culture 07478 - Baran, Stanley J. (Thomson, 2007)
This text encourages students to take more active roles as media consumers and gives them a deeper understanding of the role that the media play in both shaping and reflecting culture. Through this culture perspective, students learn that audience members are as much a part of the mass communication process as are the media producers, technologies, and industries.